The course of German history : a survey of the development of German history since 1815 - Taylor, A.J.P. (NewYork : Taylor and Francis Group, 2008)
One of A.J.P. Taylor's best-known books, The Course of German History is a notoriously idiosyncratic work, written during the last days of the Second World War. Composed in his famously witty style, yet succinct to the point of sharpness, The Course of German History is one of the great historian's finest, if more controversial, accomplishments. As Taylor himself noted, 'the history of the Germans is a history of extremes. It contains everything except moderation.' He could, of course, simply be referring to his own book.
1. Divided Germany: The Legacy of the Holy Roman Empire 2. The Ascendancy of France, 1792-1814 3. The German Confederation: The Years of Austro-Prussian Partnership, 1815-48 4. 1848: The Year of German Liberalism 5. The Ascendancy of Austria, 1849-60 6. The Conquest of Germany by Prussia, 1862-71 7. Bismarckian Germany: The Ascendancy of Prussia, 1871-90 8. The Germany of William II: The Conquest of Prussia by Germany, 1890-1906 9. The Crisis of Hohenzollern Germany, 1906-1916 10. The Rule of the German Army, 1916-19 11. Republican Interregnum, 1919-30 12. Demagogic Dictatorship and the Completion of German Unity After 1930.
Includes bibliographical references and index.
Keywords: History